Óscar Terrazas y Eudardo Preciat. Estructura territorial de la ciudad de México. México : DDF : Plaza y Valdés, 1988. 253 p. - Muñoz Contreras, María Elena (El Colegio de México A.C., 1989)
ÓSCAR TERRAZAS y EDUARDO PRECIAT, Estructura territorial de la ciudad de México, DDF y Plaza y Valdés, México, 1988